Increased levels of legumain in plasma and plaques from patients with carotid atherosclerosis. (February 2017) - Lunde, Ngoc Nguyen; Holm, Sverre; Dahl, Tuva B.; Elyouncha, Inass; Sporsheim, Bjørnar; Gregersen, Ida; Abbas, Azhar; Skjelland, Mona; Espevik, Terje; Solberg, Rigmor; Johansen, Harald Thidemann; Halvorsen, Bente
Abstract: Background and aims: The cysteine protease legumain has been shown to be up-regulated in unstable atherosclerotic plaques. This study aims to further elucidate legumain in atherosclerosis, by examining legumain in plasma and carotid plaques from patients with carotid stenosis. Furthermore, legumain secretion from monocyte-derived macrophages treated with atherogenic lipids during macrophage polarization was studied. Methods: Plasma levels of legumain from patients with carotid stenosis (n = 254), healthy controls (n = 91), and secreted from monocyte-derived macrophages were assessed by enzyme-linked-immunosorbent assay. Quantitative PCR and immunoblotting of legumain were performed on isolated plaques and legumain localization was visualized by immunohistochemistry and fluorescence microscopy. Monocyte-derived macrophages polarized to M1 or M2 macrophages were treated with VLDL, oxLDL or cholesterol crystals (CC) and the level of legumain analysed. Results: Patients with carotid stenosis had significantly higher levels of plasma legumain compared with healthy controls (median 2.0 versus 1.5 ng/ml, respectively; p = 0.003), although there was no correlation between the level of legumain and the degree of stenosis, and legumain was not an independent factor to identify patients with carotid plaques. Moreover, patients with symptoms the last 2 months had higher expressions of mature legumain, cystatin C and E/M, and the macrophage markers CD80 (M1) and CD163 (M2). Legumain co-localized with both M1 and M2 macrophages within plaques, whereas legumain mRNA expression was significantly higher ( p < 0.0001) in plaques compared to non-atherosclerotic arteries (controls). Furthermore, in vitro studies showed significantly increased secretion of legumain from pro-inflammatory M1 compared to pro-resolving M2 macrophages (p = 0.014), and particularly in M1 treated with CC. In plaques, legumain was localized to structures resembling foam cells. Conclusions: Legumain is increased in both plasma and plaques of patients with carotid stenosis and might be a new and early biomarker of atherosclerosis. Highlights: The first report of cysteine protease legumain quantification in plasma from patients with carotid stenosis. Elevated plasma legumain in patients versus controls, which can be used as an early marker of atherosclerotic disease. Plaques from patients with recent symptoms has increased legumain expression. Legumain is localized with pro-inflammatory M1 and pro-resolving M2 macrophages, as well as foam cells, in carotid lesions. Secretion of legumain is significantly higher from M1 than M2 macrophages.